Usulan Perbaikan Kualitas Proses Produksi Wafer Abon dengan Metode Six Sigma - Riyan Riyan; Heksa Bekti Ariyono (Universitas Bunda Mulia, 2017)
This paper discusses a conducted research in the food industry with a variety of snack products such as bread, cream wafers, cookies, wafer sticks, chocolate, and dry cake. The company should always improve the quality of processes and products according to customer demands. Six Sigma method is expected to improve the quality of process and product in the company. Six Sigma is a quality system approach to be used in the industrialization function engaged in the manufacturing and services sectors. Generally, six sigma strategy utilizes DMAIC approach (Define-Measure-Analyze-Improve-Control). This research focused on product wafers abon, because it contributed a large number of defects. Moreover, this paper discusses two main processes:1. oven and cooling sheet process, 2. creaming and pressing process. The improvement is focused in the creaming and pressing process, because it presents 65% of defects. Based on the obtained data processing, COPQ for 1 month is Rp. 65,473,200, - and there are 3 priority CTQ’s in the issues, Pasta Tidak Rata (53.68%), Crashed Edge (16.29%), and Crack (16.12%). Results of capability process are 91.51% and sigma level of wafer abon product is 3.647628 sigma. An analysis has been done by brainstorming to find the cause of the defect and then arranged in a fishbone diagram and five why’s diagram. Proposed improvements including to create specification given standards for setup oven and creaming machine.Keyword: Quality Control, Six Sigma, DMAIC